Analisis Peran SDM dalam Keberhasilan Capaian Akreditasi Paripurna di Rumah Sakit X Pekalongan - Caesar al Ahmed Daminggo; Chriswardani Suryawati; Septo Pawelas Arso (Jurnal Manajemen Kesehatan Indonesia, 2022)
Health services require quality service and good patient safety on an ongoing basis, and accreditation is considered a powerful method to improve the quality of health services. This study aims to describe and analyze the role of leadership and motivation in achieving accreditation at RS X Pekalongan. This research is a qualitative descriptive study. Information was obtained through in-depth interviews, observation, and document review. The sampling technique used purposive sampling, with the number of main informants as many as 19 respondents and triangulation informants as many as 4 respondents. Based on the research results, all parties in the hospital play a role in the accreditation process and all employees have their respective roles. The leadership of the director in accreditation is very good, as evidenced by the design of tasks that can be carried out properly, and in terms of increasing employee motivation, the director has provided rewards both material and non-material, as well as training according to standards. . In maintaining the results of its accreditation, the hospital instills a sense of responsibility for accreditation to all employees. Hospital owners provide moral support to hospitals by participating in a series of accreditation survey events, providing useful input during meetings and also approving funding proposals related to accreditation. Keywords: Accreditation, leadership, motivation, achievement of accreditation